Alfred F. Whiting: textes choisis/Selected Essays - Clément, Daniel; Whiting, Alfred F. (Anthropologica, 2022)
After a brief biographical note on A.E Whiting (1912-78), two unpublished essays by this author are presented. The first is an unpublished paper which he delivered in 1938 at the Annual Meeting of the Michigan Academy of Science, Arts and Letters. This is one of the very first theoretical reflections on the definition of ethnobotany at a time when the discipline was just emerging from its infancy. The second, written in the 1940s, was far ahead of its time. It contains in embryonic form the essence of all future developments of the discipline: the importance of the linguistic aspect of the ethnobotanist's work, necessity of comparative studies, analysis of meaning and etymology, historical reconstruction, borrowing phenomena, correspondence between Western and vernacular systems, etc.